Search for new physics with dijet angular distributions in proton-proton collisions at root S = 13 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; Fruehwirth,R; et al. (Journal of High Energy Physics, 2017)
A search is presented for extra spatial dimensions, quantum black holes, andquark contact interactions in measurements of dijet angular distributions in proton-protoncollisions at √s = 13 TeV. The data were collected with the CMS detector at the LHCand correspond to an integrated luminosity of 2.6 fb−1. The distributions are found tobe in agreement with predictions from perturbative quantum chromodynamics that includeelectroweak corrections. Limits for different contact interaction models are obtained.In a benchmark model, valid to next-to-leading order in QCD and in which only lefthandedquarks participate, quark contact interactions are excluded up to a scale of 11.5and 14.7 TeV for destructive or constructive interference, respectively. The productionof quantum black holes is excluded for masses below 7.8 or 5.3 TeV, depending on themodel. The lower limits for the scales of virtual graviton exchange in the Arkani-HamedDimopoulos-Dvalimodel of extra spatial dimensions are in the range 7.9–11.2 TeV, and arethe most stringent set of limits available.